Video-assisted thoracic surgery for cancer after thoracic aortic aneurysm repair. (February 2016) - Taylor, Lauren J; Adesoye, Taiwo; Maloney, James D
Video-assisted thoracoscopic surgery is increasingly accepted as an alternative to open thoracotomy and has established efficacy in the management of non-small-cell lung cancer, but the presence of extensive intrapleural adhesions has been considered a deterrent to a minimally invasive approach. We report the successful use of video-assisted thoracoscopic surgery in 3 patients with history of open thoracic aortic aneurysm repair who presented with left lower lobe stage I non-small-cell lung cancer. While this approach is feasible, it is technically demanding and thus, at the present time, we recommend that its use be limited to high-volume video-assisted thoracoscopic surgery centers.